Filmic representations of radicalization and terrorism: The silver screen as a catalyst for social science. (September 2019) - Cantey, Seth
Recent years have seen increased attention to depictions of terrorism in film and, as a consequence, scholars have learned a great deal about why and how such films are made. Too often, however, work in this area has been confined to examination of the film(s) in question, where links between what appears on the silver screen and lived experience are implied but not fully explored. Grounded in the rapidly-growing literature on pop culture and world politics, this article seeks to bridge that gap by showing that comparative film analysis can serve as a catalyst for social scientific inquiry into terrorism. By exploring how Third Cinema films communicate motivations for and doubts about the use of violence, it generates questions for social scientific inquiry that might otherwise go unasked.